Approach to frontline therapy in elderly chronic lymphocytic leukemia patients. (June 2013) - Benjamini, Ohad; Ferrajoli, Alessandra; Keating, Michael J
Although the majority of chronic lymphocytic leukemia patients are diagnosed at an older age, most of our knowledge is based on data from clinical trials of young patients. Hence, not all the prognostic factors are valid in the elderly and no standard treatment has been established. Elderly patients are heterogeneous in their competency to tolerate treatment and most require treatment modifications. Recent studies are focusing on the incorporation of dose-attenuated regimens, less myelotoxic drugs and new therapies. Monoclonal antibodies, immunomodulatory drugs and small molecules, such as B-cell receptor pathway inhibitors, may dramatically change the treatment options for and outcome of elderly chronic lymphocytic leukemia patients.